The nomenclature and taxonomy of Kalanchoe nyikae (Crassulaceae subfam. Kalanchooideae), a little-known species from East Africa - Smith, Gideon F.; Figueiredo, Estrela (Phytotaxa, 2020)
From the 1950s to the 1980s the East African taxa of Kalanchoe Adanson (1763: 248) (Crassulaceae subfam. Kalanchooideae) received taxonomic attention in a series of papers by Cufodontis (1957, 1958, 1965, 1967, 1969), Raadts (1977, 1979, 1984, 1985, 1989), and Wickens (1982, 1987) that culminated in the treatment of the genus by Wickens (1987: 30–58) for the Flora of Tropical East Africa (FTEA; Uganda, Kenya, Tanzania). Wickens (1987) recognised 25 Kalanchoe species in the FTEA region, with two species, K. ndorensis Schweinfurth (1892: 865 [as name only in Engler (1892: 232)]) and K. stuhlmannii Engler (1895: 188), treated as imperfectly known.